Emotion regulation contributes to the development of diabetes distress among adults with type 1 diabetes. Issue 1 (January 2018) - Fisher, Lawrence; Hessler, Danielle; Polonsky, William; Strycker, Lisa; Guzman, Susan; Bowyer, Vicky; Blumer, Ian; Masharani, Umesh
Highlights: We showed that 3 emotion regulation mechanisms formed a single factor. Emotion regulation was directly related to level of diabetes distress (DD). Pathways from emotion regulation to DD affected management and glycemic outcomes. Abstract: Objective: To demonstrate how maladaptive emotion regulation (ER) can lead to diabetes distress (DD), with subsequent effects on management and metabolic outcomes among adults with type 1 diabetes. Methods: Data are based on pre-intervention assessment for a random controlled trial to reduce DD. Patients were recruited in California, Oregon, Arizona and Ontario, Canada. After screening and consent, patients completed an online assessment and released their most recent laboratory HbA1C. Structural equation modeling was used to define an ER measurement model and test for significant pathways. Results: Three ER mechanisms combined into a single construct: emotion processing, non-judgment of emotions, non-reactivity to emotions. Models indicated a significant pathway from ER and cognitions to DD to disease management to metabolic control. Conclusions: As hypothesized, the three ER mechanisms formed a single, coherent ER construct. Patients with poor ER reported high DD; and high DD was linked to poor diabetes management and poor metabolic control. Practice implications: Identifying both the level of DD and the ER mechanisms that lead to high DD should be explored in clinical settings. Helping T1Ds to become more aware, less judgmental and less reactive behaviorally to what they feel about diabetes and its management may reduce DD.